STANDARDS OF EFL TEACHER PREPARATION FOR MASTER DEGREE PROGRAMS: TESOL EXPERIENCE - Кокор, М. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article is dedicated to the research ofapproaches andprinciples of EFL teacher preparation programs based on the analysis of contemporary Ukrainian programs and TESOL standards. Comparative analysis of the aspects of EFL teacher preparation in Ukraine and the USA has revealed a few considerable differences, such as: aim (theoretical vs applicable), principles (principle-based vsdomain-based), and expected outcomes (knowledge and skills vs competencies). It has been found in the researchthat EFL teacher preparation standards for Master degreein Ukraine are non-existent and therefore current domestic training programs have no clear guidelines (criteria and indicators) as tothe development of professional competence. Based on the research results the following recommendations have been madefor standards development: to define the criteria and performance indicators, develop them based on domain approach and actual needs of labor market in Ukraine and abroad; include a standard of professional development